Bioactivities, heavy metal contents and toxicity effect of macroalgae from two sites in Madura, Indonesia - Sin War Naw; Nwet Darli Kyaw Zaw; Nanik Siti Aminah; Mochammad Amin Alamsjah; Alfinda Novi Kristanti; Aondohemba Samuel Nege; Hnin Thanda Aung (Journal of the Saudi Society of Agricultural Sciences, 2020)
Sargassum duplicatum and Padina tetrastromatica seaweed species collected from oil and a non-oil extraction site at Madura Island were investigated in this study for selected bioactivities, heavy metals and toxicity effects. The collected seaweeds were evaluated for their phytochemical constituents, total phenolic contents (TPC), antioxidant activities, antidiabetic activities, anticancer activities, toxicities and heavy metals using Folin-Ciocalteus method, the 2,2-diphernyl-1 picrylhydrazyl (DPPH), α-glucosidase enzyme, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), Brine Shrimp Lethality Test (BSLT) and atomic absorption spectrophotometer, respectively. The crude extracts (C), normal hexane (N), ethyl acetate (E), and methanol residue fractions (M) were studied. The highest TPC (589.79 ± 7.14 mg GAE/g) was observed in ethyl acetate fraction of P. tetrastromatica from the non-oil extraction site. Meanwhile, the crude extracts and all fractions showed potent antioxidant, antidiabetic, and cytotoxic activities with ethyl acetate fraction of P. tetrastromatica from non-oil extraction site displaying the highest effects (IC50 25.25 ± 5.15, 249.12 ± 1.77 and 70.56 ± 2.56 µg/mL: antioxidant, antidiabetic, cytotoxic activities respectively). In the brine shrimp assay, the crude extracts and all fractions of both species from the two sites were non-toxic with exception of the hexane fraction of P. tetrastromatica from oil site which was very toxic after 24 h incubation. However, the crude extract of S. duplicatum and ethyl acetate fraction of P. tetrastromatica from oil extraction site were mildly toxic except the hexane fraction of P. tetrastromatica from oil site which was very toxic after 48 h incubation while samples of both species from the non-oil site were nontoxic. In each species, the concentration of Cd from the oil extraction site was higher than those of the non-oil site with the values of P. tetrastromatica leading and a similar observation occurred Cu in P. tetrastromatica but the same Cu was negligible in S. duplicatum as Pb was negligible in both species. According to the findings of this current study, it is safe to conclude that both S. duplicatum and P. tetrastromatica from Madura Island have antioxidant, antidiabetic and cytotoxic activity, we therefore recommend these species from the non-oil extraction site for drug candidates against the various health abnormally they seem to inhibit.